Application of bacterial isolates to mitigate the effects of salt stress on red chilli growth and yields - Nurul Aini; Wiwin Sumiya Dwi Yamika; Luqman Qurata Aini; Puput Wahyuningsih (Journal of Degraded and Mining Lands Management, 2019)
The objective of this research was to study the effect of bacterial isolates on red pepper at the saline condition. The research conducted in the station of Brawijaya University in Jatikerto village, Malang regency. The study used a randomized block design with bacteria isolated from the soil of saline-prone regions of Lamongan, in coastal East Java Indonesia. The treatments consisted of P0: saline soil without bacteria, P1: saline soil + bacteria SN 13, P2: saline + bacteria SN 22, P3: saline soil + bacteria SN 23, P4: saline soil + bacteria (SN 13 + SN 22), P5: saline soil + bacteria (SN 13 + SN 23), P6: saline soil + bacteria (SN 22 + SN 23), and P7: saline soil + bacterial (SN 13 + SN 22 + SN 23). Red chilli variety used was Gada MK F1. The results showed that the application of bacterial isolates increased leaf area, dry weight of roots and shoot. Uptake of N, P, K and Na also increased with bacterial isolate application. The number of fruit and fruit weight increased by 11.94% and 15.93%, respectively, compared with no bacteria. Proline content increased with the application of bacterial, while the capsaicin content decreased.